Social Welfare and Poverty Reduction Activities of NGOs in Bangladesh: An Empirical Study - Sultana, Shirin; Uddin, Md. Nasim (Asian Business Review, 2022)
Bangladesh is both a developing nation and a medium-sized economic power. It is among the eleven market-based middle-income countries with the fastest expanding economies. It is the forty-second market-based economy on the planet in nominal terms and the thirty-first largest by purchasing power parity. According to the IMF, Bangladesh's economy is the second biggest country on an upswing in 2016, with an annual rate of 7.1%. Since the early 2000s, Bangladesh's poverty has unexpectedly decreased, accelerating economic growth. Non-governmental organizations (NGOs) actively contribute to the decline of extreme poverty in our nation. NGOs engaged in some charitable work and improved social welfare. This study's primary goal is to show how NGOs and their initiatives affect Bangladesh's social welfare and poverty reduction. Researchers have used primary and secondary data and powerful statistical tools to assess pertinent data to accomplish these goals. From the researchers' observations, data analysis, and findings, it is clear that NGO programs significantly promote social welfare and reduce poverty in Bangladesh.